PETROLOGY OF MANTLE PERIDOTITES AND INTRUSIVE MAFIC ROCKS FROM THE KERMANSHAH OPHIOLITIC COMPLEX (ZAGROS BELT, IRAN): IMPLICATIONS FOR THE GEODYNAMIC EVOLUTION OF THE NEO-TETHYAN OCEANIC BRANCH BETWEEN ARABIA AND IRAN - Allahyari, Khalil; Saccani, Emilio; Pourmoafi, Mohamad; Beccaluva, Luigi; Masoudi, Fariborz (Ofioliti, 2010)
The Kermanshah ophiolitic complex consists of a mélange formation, which includes dismembered ophiolitic sequences. These ophiolites are located along the Main Zagros Reverse Fault, which marks the ophiolitic suture zone between the Zagros belt and the Sanandaj-Sirjan zone. They represent the Neo- Tethyan oceanic lithosphere, which originally existed between the Arabian (to the south) and Eurasian (to the north) continental margins. The Kermanshah ophiolites were emplaced onto platform carbonate rocks, which represented the northeastern Arabian margin.The Kermanshah ophiolitic complex is composed of various partial sequences, which are represented by: (1) mantle tectonites consisting of depleted lherzolites and both clinopyroxene- (cpx-) rich and cpx-free harzburgites; (2) a troctolite-cumulate gabbro-isotropic gabbro sequence mainly showing pegmatoid texture; (3) a wehrlite-cumulate gabbro-isotropic gabbro sequence showing foliated texture; (4) a dyke complex; (5) very scarce pillow basalts. Mantle tectonites are volumetrically predominant and tectonically overlay the gabbroic sequences. A number of conclusions may be drawn based on petrographic observations, mineral chemistry, whole-rock chemistry, and rare earth elements (REE) modelling carried out on both mantle tectonites and intrusive rock associations. (1) The Foliated Gabbro Unit has an N-MORB chemical signature and represents a portion of oceanic crust generated in a mid-ocean ridge setting from an N-MORB-type sub-oceanic mantle. (2) The Pegmatoid Gabbro Unit displays an E-MORB signature and represents a portion of oceanic crust most likely generated from a sub-oceanic mantle source enriched in light REE (LREE). A comparison with the well-studied Oman ophiolites suggests that this sequence may have formed during the early stage of oceanic spreading. (3) The depleted lherzolites present mild depletions in heavy REE (HREE) and variable depletion in LREE. REE modelling shows that they may represent a residual mantle after 15-20% removal of N-MORB melts. Some lherzolites show a moderate enrichment in La and Ce with respect to Sm, suggesting that this residual MORB mantle was subsequently trapped in a supra-subduction zone (SSZ) mantle wedge and enriched in LREE by subduction-derived fluids. (4) The depleted harzburgites present a significant depletion in incompatible elements and REE, coupled with a marked LREE enrichment with respect to medium REE. REE modelling shows that they may represent a residual mantle after 25-30% removal of boninitic-type melts in an intra-oceanic arc setting.